Tribological aspects of the railway wheel - rail contact - Beneš, Libor; Kaloč, Rudolf; Kout, Jan (Univerzita Pardubice, 2007)
It is implicit that the primary cause of the creation of effects that appear in the contact area of two real bodies (railway wheel-rail) are the force effects causing reversible as well as irreversible material changes in the surface layers. The main goal of this work is to point out the existence of contact temperatures which obviously significantly influence the character of the processes. It is surprising that this phenomenon has not been taken into account yet, especially in the theory of adhesion shift. The concept of the research in this field stems from the belief of the authors that it is necessary, apart from the history of loading, to monitor the cooperation of abrasive processes in the contact area in connection with the definition of limiting conditions in the surface layers as processes which represent the initiatory processes of the potential (catastrophic) damage of a wheel.
Tribologické aspekty v kontaktu mezi železničním kolem a kolejnicí
Keywords: kontaktní teploty; železniční kola - kolejnice; adhezní přenos; tribologické aspekty